Genetic Engineering Strategies for Euglena gracilis and Its Industrial Contribution to Sustainable Development Goals: A Review - Harada, Ryo; Nomura, Toshihisa; Yamada, Koji; Mochida, Keiichi; Suzuki, Kengo (Frontiers in Bioengineering and Biotechnology, 2020)
The Sustainable Development Goals (SDGs) adopted at the 2015 United Nations Summit are globally-applicable goals that are designed to help countries realize a sustainable future. To achieve these SDGs, it is necessary to utilize biological resources, among other available resources. In recent years, bioeconomy has been an attractive concept for achieving the SDGs. Microalgae are one of the biological resources that show promise in realizing the “5F”s (food, fiber, feed, fertilizer, and fuel). Among the microalgae, Euglena gracilis has the potential to qualify as a “5F” owing to its unique features that are lacking in other microalgae. E. gracilis has already been produced on an industrial scale for use as an ingredient in functional foods and cosmetics. In recent years, genetic engineering methods for breeding E. gracilis have been researched and developed to achieve higher yields. In this article, we summarize how microalgae contribute towards achieving the SDGs. We focus on the contribution of E. gracilis to the bioeconomy, including its advantages in industrial use and the characteristics that are unique to this species. In addition, we review genetic engineering-related research trends centered around E. gracilis, including a complete nuclear genome determination project, genome editing technology using the CRISPR-Cas9 system, and the development of a screening method for selecting useful strains.